Cognitive Radio-Based Vehicular Ad Hoc and Sensor Networks - Mohammad Jalil Piran; Yongwoo Cho; Jihyeok Yun; Amjad Ali; Doug Young Suh (International Journal of Distributed Sensor Networks)
Current advancements in vehicular networking lead to amplifying the issue of spectrum scarcity. Cognitive radio (CR) has emerged as the key technology that enables flexible, efficient, and reliable spectrum exploiting by unlicensed networks to use licensed spectrum bands in an opportunistic manner to alleviate the spectrum scarcity issue. We have already proposed vehicular ad hoc and sensor networks (VASNET) as a new networking paradigm for vehicular communication by utilizing wireless sensor nodes in two mobile and stationary modes. The nodes are employed to sense vehicles' activity, for example, car crashes. Like other unlicensed networks, VASNET is supposed to operate over unlicensed spectrum bands. However, due to emergency nature of accident alarms in VASNET that must be received in minimum period of time and avoiding packet loss, in this paper we investigate CR-based VASNET, named as CR-VASNET. Various challenges and issues are discussed in details. In order to save stationary nodes' power and enlarge the network lifetime, an optimization technique for relay node selection is proposed. Furthermore, for primary users (PU) protection, an energy detection-based scheme is suggested to calculate the probability of PU arrival. Our theoretical discussions and simulation results proved the efficient functionality of the proposed CR-VASNET as a promising vehicular networking paradigm.